1993
DOI: 10.1016/0014-5793(93)80366-3
|View full text |Cite
|
Sign up to set email alerts
|

The primary structure of inhibitor of cysteine proteinases from potato

Abstract: The complete amino acid sequence of the cysteine proteinase inhibitor from potato tubers was determined. The inhibitor is a single-chain protein having 180 amino acid residues. Its primary structure was elucidated by automatic degradation of the intact protein and sequence analysis of peptides generated by CNBr, trypsin and glycyl endopeptidase. A search through the protein sequence database showed homology to other plant proteinase inhibitors of different specificities and non-inhibitory proteins of M, around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 30 publications
2
30
0
2
Order By: Relevance
“…Five structurally different groups of protein cysteine proteinase inhibitors have been reported: cystatins (4), thyroglobulin type-1 domain inhibitors or thyropins (5), soybean trypsin inhibitor-like inhibitors of cysteine proteinases from potato (6), pineapple inhibitors of cysteine proteinases (7,8), and very recently, inhibitors of cysteine proteinases homologous to propeptide regions of cysteine proteinases (9). So far, only the mechanism of interaction of the cystatin superfamily of inhibitors has been elucidated (10,11), followed recently by that of thyropins (12), but overall there is very little information available on all other cysteine proteinase inhibitors concerning specificity, kinetics, and mode of binding.…”
mentioning
confidence: 99%
“…Five structurally different groups of protein cysteine proteinase inhibitors have been reported: cystatins (4), thyroglobulin type-1 domain inhibitors or thyropins (5), soybean trypsin inhibitor-like inhibitors of cysteine proteinases from potato (6), pineapple inhibitors of cysteine proteinases (7,8), and very recently, inhibitors of cysteine proteinases homologous to propeptide regions of cysteine proteinases (9). So far, only the mechanism of interaction of the cystatin superfamily of inhibitors has been elucidated (10,11), followed recently by that of thyropins (12), but overall there is very little information available on all other cysteine proteinase inhibitors concerning specificity, kinetics, and mode of binding.…”
mentioning
confidence: 99%
“…As for protease inhibitors, serine-proteinase inhibitors are dominant, but it is very interesting that potato [26] and tomato (Cathepsin D inhibitor protein-tomato, Werner, R., Guitton, M. & Muehlbach, H. P., EMBL Data Library accession no. S34387) inhibitors of cathepsin D, an aspartic proteinase, are clearly homologous to the trypsin inhibitor, and a potato cysteine proteinase inhibitor is also a homologue of soybean trypsin inhibitor [28]. Recently, it was found that the N-terminal sequence of a dehydroascorbate reductase from spinach chloroplast is similar to that of the soybean trypsin inhibitor, and that the reduced soybean trypsin inhibitor itself has the same enzyme activity [29].…”
Section: Resultsmentioning
confidence: 99%
“…The cysteine protease inhibitor PCPI 8.3, isolated from potato tubers, was classifi ed as β -trefoil on the basis of the sequence homology (Krizaj et al , 1993 ). BbCI was fi rst classifi ed as a β -trefoil inhibitor by its sequence homology (de Oliveira et al , 2001 ) and later confi rmed by its crystal structure (Hansen et al , 2007 ).…”
Section: Inhibition Of the C1 Family Cysteine Proteasesmentioning
confidence: 99%